Revision of Megascogaster (Hymenoptera, Braconidae, Cheloninae), with a new species from Sulawesi, Indonesia - Kittel, Rebecca N. (Zootaxa, 2014)
Megascogaster wallacei sp. n. is described from Sulawesi, Indonesia. This is the first representative south of the Philippines and is only the second species of this rare genus described since the type species, M. elongata Baker, 1926. The presence of Megascogaster in Sulawesi, a part of Wallacea, points to a broader distribution of the genus in Southeast Asia. A redescription of M. elongata and a description of the new species M. wallacei are presented along with a key to separate them.